PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PUSAT STATISTIK (BPS) - Raju Ardiansyah; Nizar Hamdi; Khaerul Hadi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This study aims to determine the effect of leadership style, work motivation and workenvironment on employee performance at the Central Bureau of Statistics. Based on theresults of the hypothesis test the leadership style variable has a calculated t value greater thant table, namely 3,361 > 2.026 with a significance value of 0.002 <0.05 then Ho is rejected andHa is accepted. There is a partial influence between leadership style on performance. Thework motivation variable has a calculated t value that is greater than t table, namely 2,994 >2.026 with a significance value of 0.005 <0.05, then Ho is rejected and Ha is accepted. Thereis a partial influence between work motivation on performance. The work environmentvariable has a calculated t value that is smaller than t table, namely 1,030 <2.026 with asignificance value of 0.310 > 0.05. Work environment variables partially have no effect onperformance. It can be seen that the calculated F has a greater value than the F table, namely14,206 > 3.25 with a significance level of 0,05. The coefficient of determination test(Adjusted R Square) is 0.498 or 49.8%.